(untitled) (Colombia Medica, 2011)
This review explores changes established by various groups worldwide about the concept and method of implementing the Strategy for Primary Health Care (PHC) originated in Alma Ata in 1978. It establishes four key pillars to introduce Health Systems as its axis with the APS, which are achieving universal coverage for all people, providing medical attention focused on the individual patient, promoting public health policies that benefit the entire community, and engaging in a concerted national and regional governance in all sectors that influence health determinants of individuals and their environment. The implementation of such in each health system depends on the context of each country and the growth and development rate of its health sector.